Implementation of Village Fund Allocation (ADD) Policy in Sunggumanai Village, Pattallassang District, Gowa Regency - Danal Ashar, Andi Idham; Zainal, Henni; To Taddampali, Andi Caesar (Pinisi Business Administration Review, 2023)
The financial balance system between the Central Government and Regional Governments has an emphasis on regional autonomy policies which designate districts and cities as the focus of autonomy. The purpose of this study was to determine the implementation of village fund allocation policies in Sunggumanai, Pattalassang District, Gowa Regency. The research method used is a qualitative approach. Data collection techniques are interviews, documents and observation. Data analysis techniques are data reduction, data processing and drawing conclusions. The research results show that the implementation of the Village Fund Allocation Policy (ADD) in Pattallassang District, Gowa Regency is going quite well. This can be seen from the preparation stage in the form of preparing the Village Revenue and Expenditure Budget (APBDes), implementation of each activity up to the stage of preparing accountability. However, the implementation of the ADD policy has not been optimal, this is because there is still a lack of socialization regarding the planning of ADD activities, there are still delays in completing ADD physical activities, and there are still delays in preparing accountability reports.